Implementation and Experimental Validation of Efficiency Improvement in PM Synchronous Hub Motors for Light Electric Vehicles - comezoglu, Irfan Guven; Zorlu Partal, Sibel (MDPI, 2022)
The efficiency of permanent magnet synchronous hub motors (PMSHM) used in light electric vehicles (EVs) is lower than that used in commercial EVs. Therefore, in this study a high-efficiency radial-flux outer-rotor PMSHM was designed for light EVs. The high-efficiency motor will contribute to the reduction of the power consumption demand from the batteries of EVs, the longer life of the batteries and the longer uninterrupted operation of the system. The optimization objectives, such as motor sizing, number of slots and poles, air gap length, material selection, stator winding structure, stator slot shape, magnet thickness, and cutting method for stator sheets were considered to ensure high efficiency and low cogging torque. In this study, three validation stages were followed; electromagnetic analyzes with FEM, analytical calculations, and finally experimental validation. First, the design parameters of the motor were determined based on the analyses results obtained using ANSYS Maxwell software, and then validated both with the analytical calculations and experimental results. The comparison results show that the design data of the motor at the rated speed agree well with the analytical calculations and test results. After obtaining the optimized motor design, the motor was installed on a prototype electric car for the road test. During the test drive, the motor performed successfully and operated compatibly with the rest of the electric vehicle systems such as the motor driver and the battery.
Keywords: design optimization; efficiency; electric vehicles; electromagnetic analysis; permanent magnet synchronous motor; COGGING TORQUE; DESIGN; Energy & Fuels